Planting Attitude Responsibility and Concern Through Learning Civics in School Base - Andini Purba (International Journal of Students Education, 2024)
The research results show that the cultivation of an attitude of responsibility and caring was carried out through method assignment, habituation, do task, gather task appropriate time, do task on work alone, get dressed neat, do picket school, as well as teacher and person old build communication. Effort embed attitude not quite enough answer and concern ie exemplary teacher, the active role of the principal, collaboration between teachers and parents, as well as conducting regular evaluations at the school. It can be concluded that citizenship education learning can make students behave smart and good citizenship in form student for responsible And care in school nor surrounding. The method used is a literature study, in which the author reads and reads look for topic from various source like journal, book, or source which other which felt relevant. One of the subjects in formal education is civics learning, in civics learning is really great provide a positive impact. Because in civics this is not only It's just about citizenship, but there is an instillation of values and morals, so it has a big impact positive on sustainability in effort increase mark and moral for student school base.